Analysis of the quality of health services on satisfaction, anxiety, and physical health of pregnant women - Sri Komala Dewi; Vivi Silawati; Retno Widowati; Rukmaini (KHD-Production, 2026)
Healthcare constitutes a fundamental societal necessity, wherein rising social standards have driven an intensified public demand for quality services. Within this framework, pregnant women's satisfaction with midwifery care is significantly influenced by effective communication, personalized attention, professional competence, and the adequacy of facilities at community health centers. This study aims to analyze healthcare service quality on satisfaction, anxiety, and physical health of pregnant women. This quantitative study uses a descriptive correlational approach. The respondents in this study were 246 pregnant women receiving healthcare services. The sampling technique used was stratified random sampling. Analysis was conducted using linear regression tests. The results showed a significant relationship between healthcare quality and the three variables (P < 0.001). Maternal satisfaction was the strongest factor, with a coefficient B of 5.451 and an odds ratio (OR) of 233.026. The quality of healthcare services significantly influences maternal satisfaction, anxiety, and physical health, with satisfaction being the dominant variable. Pregnant women are advised to be active with healthcare providers, undergo regular check-ups, and improve health communication literacy to improve satisfaction and physical health, as well as reduce anxiety during pregnancy.